2000
DOI: 10.1002/1097-0185(20000701)259:3<276::aid-ar50>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscope study of bacterial morphotypes on the anterior dorsal surface of human tongues

Abstract: The human tongue has been the subject of many cytological and histological studies. When a literature search disclosed no reports of the ultrastructure of the morphotypes of bacteria residing on the tongue's surface, a transmission electron microscope study of ultrathin sections of bacteria obtained by scraping eight human tongues was undertaken. The scrapings from the anterior dorsal tongue surfaces, processed conventionally for electron microscope study, revealed 33–35 different bacterial morphotypes. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To further examine the ultrastructure of its cell wall, transmission electron microscopy (TEM) of sectioned cells was performed on the L. iners KY and L. plantarum . Since it has been noted that both TEM and Gram-staining are affected by aging [ 28 , 29 ], we used cells in mid-exponential growth phases. TEM images clearly resolved cell envelopes, consisting of the plasma membrane and peptidoglycan (PG) layer ( Figure 1 d,e).…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the ultrastructure of its cell wall, transmission electron microscopy (TEM) of sectioned cells was performed on the L. iners KY and L. plantarum . Since it has been noted that both TEM and Gram-staining are affected by aging [ 28 , 29 ], we used cells in mid-exponential growth phases. TEM images clearly resolved cell envelopes, consisting of the plasma membrane and peptidoglycan (PG) layer ( Figure 1 d,e).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of tongue as a potential microbial reservoir has been suggested by some studies. A study of the ultrastructure of the morphotypes of bacteria residing to the tongue's surface showed the presence of 35 different bacterial morphotyes 1 . Tanner, et al 25 , by using checkerboard DNA probe assay, verified that some cariogenic or periodontal pathogens microorganisms were more frequently isolated from tongue than tooth samples in children under 18 months, and suggested that the tongue is an important microbial reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, binary fission was visible in both P. gingivalis and P. pallens (red arrow, Figures 2B–D ). In P. pallens ( Figure 2B ), some round bright vacuoles (blue arrows) were abundant, which are electron-lucent granules ( 24 ) The term “electron-lucent” refers to their appearance in the TEM image as loose lighter contrast aggregates. These vacuoles might be rich in lipids or other substances that do not provide significant image contrast ( 25 ).…”
Section: Resultsmentioning
confidence: 99%